Development of a rapid lateral flow immunoassay test for detection of exosomes previously enriched from cell culture medium and body fluids. Issue 1 (12th August 2016) - Oliveira‐Rodríguez, Myriam; López‐Cobo, Sheila; Reyburn, Hugh T.; Costa‐García, Agustín; López‐Martín, Soraya; Yáñez‐Mó, María; Cernuda‐Morollón, Eva; Paschen, Annette; Valés‐Gómez, Mar; Blanco‐López, Maria Carmen
Abstract : Exosomes are cell‐secreted nanovesicles (40–200 nm) that represent a rich source of novel biomarkers in the diagnosis and prognosis of certain diseases. Despite the increasingly recognized relevance of these vesicles as biomarkers, their detection has been limited due in part to current technical challenges in the rapid isolation and analysis of exosomes. The complexity of the development of analytical platforms relies on the heterogeneous composition of the exosome membrane. One of the most attractive tests is the inmunochromatographic strips, which allow rapid detection by unskilled operators. We have successfully developed a novel lateral flow immunoassay (LFIA) for the detection of exosomes based on the use of tetraspanins as targets. We have applied this platform for the detection of exosomes purified from different sources: cell culture supernatants, human plasma and urine. As proof of concept, we explored the analytical potential of this LFIA platform to accurately quantify exosomes purified from a human metastatic melanoma cell line. The one‐step assay can be completed in 15 min, with a limit of detection of 8.54×10 5 exosomes/µL when a blend of anti‐CD9 and anti‐CD81 were selected as capture antibodies and anti‐CD63 labelled with gold nanoparticles as detection antibody. Based on our results, this platform could be well suited to be used as a rapid exosome quantification tool, with promising diagnostic applications, bearing in mind that the detection of exosomes from different sources may require adaptation of the analytical settings to their specific composition.